Hybrid Learning: Strategies to Attract Student Learning Interests and Outcomes on Post Pandemic - Ni Wayan Karmini; M. Nurzen S.; Trinandari Prasetyo Nugrahanti; Iwan Ramadhan; Rusliandy Rusliandy; Tekat Sukomardojo (AL-ISHLAH: Jurnal Pendidikan, 2023)
The hybrid learning model, also called "mixed learning," is a way to move towards an efficient new normal. Hybrid learning includes both in-person and online meetings that are planned ahead of time so that learning goals can be communicated directly during face-to-face learning. So, the goal of this study was to look at how the hybrid learning model could be used as a way to get post-pandemic students interested in learning and improve their understanding when using full distance learning mode. This was a descriptive, qualitative study that used an open-ended survey method with a Google Form questionnaire that was sent out online through a WhatsApp social media group. There were 126 students from the 11th grade at a state senior high school in Denpasar who took part. The results showed that when the mixed learning method was used to get students interested in learning Indonesian, math, and religion, and when it was used in the learning process in class, the average learning outcomes changed for the better. This is because of a new way of learning called "hybrid learning," which makes it easier for students to catch up if they miss class for some reason. The distance to school saves a lot of time because they don't have to go every day. This can make students more interested in learning.